Pengaruh Kepercayaan Merek, Kualitas Layanan, dan Promosi Digital Terhadap Minat Beli Ulang Pengguna Shopeefood di Kalangan Mahasiswa Universitas Wijaya Kusuma Surabaya - Sari, Mawar; Giyana (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2025)
his research focuses on examining how brand trust, service quality, and digital marketing affect the likelihood of ShopeeFood users to make repeat purchases, particularly among students at Wijaya Kusuma University in Surabaya. The investigation employs a quantitative method that involves a survey, with questionnaires being distributed to 100 participants from eight different faculties at Wijaya Kusuma University, selected through a purposive sampling approach. Data collected were analyzed using multiple linear regression with the help of SPSS software. Findings indicate that brand trust, service quality, and digital marketing positively and significantly influence the intention to repurchase among ShopeeFood users, both independently and together. This research offers an empirical insight into the elements impacting repurchase intentions in digitally based service applications. In conclusion, the study highlights that enhancing brand trust, refining service quality, and improving digital marketing strategies are essential tactics to influence consumer behavior among students at Wijaya Kusuma University, Surabaya.